Critical Perspectives: Students' expectations of difficulties they may face in undertaking their degree - Briguglio, Carmela; Howe, Julie (HERDSA, 2006)
This paper examines students’ concerns about completing tertiary studies in an Australian context. Qualitative data were collated from a short writing task undertaken by a group of undergraduate students in the Curtin Business School for the purpose of diagnosing students’ writing skills. The task required students to discuss challenges they expected to face in the course of their studies. The data indicated that although both local and internationalstudents have some common concerns, there are subtle differences in what this means for the different sub-groups. The concerns of international students, in particular, support previous research in the field, and indicate that they have realistic expectations of the challenges they will face. Nevertheless, many students reveal a positive approach to facing any future challenges and a strong desire to apply themselves fully and to be successful. Unlike much existing research in this field, which has tended to be based on data gathered from students either during their degree studies or at the end of their first year, the data for this paper were obtained at the beginning of the first year.